DISINFORMATION AND DIGITAL ELECTION CRIMES: CHALLENGES FOR DEMOCRACY (TACKLING FAKE NEWS AND THE USE OF ARTIFICIAL INTELLIGENCE IN CAMPAIGNS) (CIPEEX, 2025)
The present work aims to discuss the impacts of misinformation and digital electoral crimes on democracy, focusing on Brazilian political campaigns. With the advancement of technologies and the increasing use of artificial intelligence, the virtual environment has become a fertile ground for the dissemination of false information, especially during election periods. So-called fake news spreads rapidly through social networks and is fueled by algorithms and automated profiles. These practices compromise the electoral process by influencing public opinion based on distorted or fraudulent content. In addition, resources like deepfakes have been used to simulate candidates' speeches, confusing voters and violating the principle of true information. Despite the existence of legal provisions, such as the Electoral Code and Law No. 9,504/1997, legislation still faces challenges in keeping up with technological advancements and effectively combating misinformation digital crimes are effective. The Electoral Justice has sought answers but lacks more modern and effective mechanisms. Thus, the work proposes measures such as normative improvement, the development of preventive strategies, and investment in media education. Raising voter awareness and holding agents involved in misinformation accountable are fundamental paths to ensure fairer and more transparent elections. KEYWORDS: Misinformation. Elections. Fake news. Artificial intelligence. Democracy.